An investigation of the relationship between journalists and their news sources: a case study of The Post newspaper in Zambia - Kabeta, Jacqueline Milambo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2006)
Normative professional journalism and the need to re-evaluate the structural social context of journalism practice and its role in emerging democracies has led to the increased scrutiny of journalists and their relationship to news sources. This study conceptualises the relationship between journalists and news sources as a dual process of consensus and conflict of interests in the newsgathering practice in Zambia, an emerging democracy. The study suggests that journalists actively pursue powerful individuals in society such as those in government, pressure groups and business as news sources who have been available and suitable in the past. Journalists' view of society as bureaucratically organised and the short turn-around time of news production are among the organisational factors attributed to this tendency. This study adopts a sociological approach to investigate the journalist-news source relationship at The Post, in Zambia, by factoring in the perspectives of social organisation of newswork and political economy. Whereas the social organisation perspective focuses on the organisational and occupational demands of journalists, political economy reinforces the larger context of journalist-news source interaction in a society. Additionally, the social constructivist theory, which is premised around the idea that the agenda and content of journalism production, is in part a product of non-journalistic social factors is useful in understanding the various influences on the relationship. The study investigates the nature of the journalist-news source relationship using two diametrically opposed views "“ the dominant (exchange) and competitive (adversarial) paradigms. This is aimed at establishing whether the relationship is an exchange or adversarial. While the latter relationship is common in liberal democracies where the media are seen as part of elite structures with considerable power on their own, the thinking is that inequalities in resource distribution and political power generate social tensions in developing countries that require media to be carefully managed. Using qualitative semi-structured interviews and observation methods, this study establishes that while the adversarial role has an attraction for the journalists investigated, the exchange model comes closest to describing the nature of relationship they share with their news sources.
Keywords: The Post (Zambia); Newspapers -- Zambia; Journalism -- Zambia; Journalists -- Zambia; Reporters and reporting -- Zambia